Phosphorous recovery from sewage sludge using calcium silicate hydrates - Lee, Chang-Gu; Alvarez, Pedro J. J.; Kim, Hee-Gon; Jeong, Seongpil; Lee, Seunghak; Lee, Ki Bong; Lee, Sang-Hyup; Choi, Jae-Woo (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Phosphorous is an essential limiting nutrient for which there is no substitute. Its efficient recovery from sewage treatment plants is important to mitigate both dependence on limited reserves of exploitable phosphate rock and eutrophication of surface waters. Here, we evaluate the use of calcium silicate hydrates (CSH) to recover phosphorous eluted from sewage sludge. Phosphorous elution experiments were conducted with acid and base leaching solutions. The phosphorous recovery efficiency with CSH was compared to that with other calcium compounds, and the final product was analyzed to assess its potential value as fertilizer. Dried sewage sludge from the West Lake Ecological Water Resource Center, South Korea, having 123 g-P kg(-1), was used for these tests. About 55% of the phosphorus in the sludge was released with an elution solution of 0.1 M H2SO4. A dose of 15 g L-1 of CSH recovered 89.6% of the eluted phosphorous without the need for additional pre-treatment, and the resulting calcium phosphate product (in brushite form, based on XRD analysis) exhibited superior settleability than that resulting from Ca(OH)(2)(-) and CaCl2-induced precipitation. XRD peaks of the calcium sulfate hydrate (in gypsum form) and residual CSH were also observed. The final product contained a relatively high content of the total P2O5 eluted in a 2% citric acid solution (43.1%), which suggests that it might be readily used to fertilize crops. (C) 2017 Elsevier Ltd. All rights reserved.